FAKTOR YANG BERHUBUNGAN DENGAN STUNTING PADA BALITA USIA 24-56 BULAN - Desy Rahmawati,; M. Ridwan,; Firda Fibrila, (JOEL: Journal of Educational and Language Research, 2022)
The case of stunting in toddlers is still a health problem that needs to be watched out for and needs to be seen as an important issue to overcome because it is related to child welfare. Research finds out factors related to stunting incidence in toddlers aged 24-60 months. Analytical survey research method with cross sectional design. The subjects were all toddlers aged 24-60 months who met the inclusion and exculpatory criteria totaling 948 toddlers with a large sample of 88 toddlers. Data were collected simple random sampling by analyzing the chi square test. The results of the study obtained 11.4% of toddlers stunted, 28.4% of mothers with less knowledge, 36.3% of mothers at high risk, and 42% of family income in the low category. Results: the relationship of maternal knowledge with the incidence of stuntung p-value 0.028, the relationship of maternal age of p-value stuntung event of 0.033, and the relationship of family income with the incidence of stuntung p-value 0.015. Conclusion: there is a relationship between knowledge, maternal age and family income with the incidence of stunting in toddlers aged 24-60 months. Examination of children's growth and development using KTSP needs to be carried out continuously as an effort to early detect and assess the nutritional status of toddlers by involving all elements.